Development of Dynamic Signal Analyzer Virtual Instrument (DSA VI): A Research Proposal - Asmara Yanto; Anrinal Anrinal (Jurnal Teknik Mesin (JTM), 2016)
At present, one of the maintenance types that is being developed is the predictive maintenance based on the mechanical signals obtained by performing the mechanical quantities measurements. In general, a mechanical signal is a dynamic signal where to acquire this signal, it is required a dynamic signal analyzer (DSA) instrument.  However, the availability of DSA instruments in the market is limited in functionality and specification and also high cost. Therefore, in this work, a DSA instrument in the form of computer-based virtual instrument (DSA VI) would be developed. The DSA VI would designed by using the LabVIEW software and an Arduino UNO hardware. It is hopefully that the developed DSA VI capable to acquiring, processing, displaying, storing and reading the measured mechanical signals.